SPIRIT 2025 statement: Updated guideline for protocols of randomised trials. - An-Wen Chan; Isabelle Boutron; Sally Hopewell; David Moher; Kenneth F Schulz; Gary S Collins; Ruth Tunn; Rakesh Aggarwal; Michael Berkwits; Jesse A Berlin; Nita Bhandari; Nancy J Butcher; et al. (PLoS Medicine)
Importance The protocol of a randomised trial is the foundation for study planning, conduct, reporting, and external review. However, trial protocols vary in their completeness and often do not address key elements of design and conduct. The SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) statement was first published in 2013 as guidance to improve the completeness of trial protocols. Periodic updates incorporating the latest evidence and best practices are needed to ensure that the guidance remains relevant to users. Objective To systematically update the SPIRIT recommendations for minimum items to address in the protocol of a randomised trial. Design We completed a scoping review and developed a project specific database of empirical and theoretical evidence to generate a list of potential changes to the SPIRIT 2013 checklist. The list was enriched with recommendations provided by lead authors of existing SPIRIT/CONSORT (Consolidated Standards of Reporting Trials) extensions (Harms, Outcomes, Non-pharmacological Treatment) and other reporting guidelines (TIDieR). The potential modifications were rated in a three-round Delphi survey followed by a consensus meeting. Findings Overall, 317 individuals participated in the Delphi consensus process and 30 experts attended the consensus meeting. The process led to the addition of two new protocol items, revision to five items, deletion/merger of five items, and integration of key items from other relevant reporting guidelines. Notable changes include a new open science section, additional emphasis on the assessment of harms and description of interventions and comparators, and a new item on how patients and the public will be involved in trial design, conduct, and reporting. The updated SPIRIT 2025 statement consists of an evidence-based checklist of 34 minimum items to address in a trial protocol, along with a diagram illustrating the schedule of enrolment, interventions, and assessments for trial participants. To facilitate implementation, we also developed an expanded version of the SPIRIT 2025 checklist and an accompanying explanation and elaboration document. Conclusions and relevance Widespread endorsement and adherence to the updated SPIRIT 2025 statement have the potential to enhance the transparency and completeness of trial protocols for the benefit of investigators, trial participants, patients, funders, research ethics committees, journals, trial registries, policymakers, regulators, and other reviewers.